Endothelial Cell Surface Expressed Chemotaxis and Apoptosis Regulator (ECSCR) Regulates Lipolysis in White Adipocytes via the PTEN/AKT Signaling Pathway - Kilari, Sreenivasulu; Cossette, Stephanie; Pooya, Shabnam; Bordas, Michelle; Huang, Yi-Wen; Ramchandran, Ramani; Wilkinson, George A. (PLOS ONE, 2015)
Elevated plasma triglycerides are associated with increased susceptibility to heart disease and stroke, but the mechanisms behind this relationship are unclear. A clearer understanding of gene products which influence plasma triglycerides might help identify new therapeutic targets for these diseases. The Endothelial Cell Surface expressed Chemotaxis and apoptosis Regulator (ECSCR) was initially studied as an endothelial cell marker, but has recently been identified in white adipocytes, the primary storage cell type for triglycerides. Here we confirm ECSCR expression in white adipocytes and show that Ecscr knockout mice show elevated fasting plasma triglycerides. At a cellular level, cultured 3T3-L1 adipocytes silenced for Ecscr show a blunted Akt phosphorylation response. Additionally we show that the phosphatase and tensin homology containing (PTEN) lipid phosphatase association with ECSCR is increased by insulin stimulation. These data suggest a scenario by which ECSCR contributes to control of white adipocyte lipolysis. In this scenario, white adipocytes lacking Ecscr display elevated PTEN activity, thereby reducing AKT activation and impairing insulin-mediated suppression of lipolysis. Collectively, these results suggest that ECSCR plays a critical function in regulating lipolysis in white adipose tissue.